Validitas dan Praktikalitas e-LKPD Berbasis Project pada Materi Termokimia di Sekolah Menengah Atas untuk Meningkatkan Hasil Belajar Peserta Didik Kelas XI - Azla Ismathulhuda; Hardeli Hardeli; Alizar Alizar; Yerimadesi Yerimadesi (Jurnal Penelitian Pendidikan IPA, 2022)
In the 21st century with the industrial era 4.0, teachers and students are required to be technology literate. Then, the Covid-19 that emerged at the end of 2019 greatly affected the education sector. One of the chemistry materials in class XI in exact fields that are quite difficult to understand is thermochemistry because it is abstract. Learning models that guide students to learn independently, such as the Project Based Learning (PjBL) model are needed. The purpose of this study was to develop electronic teaching materials in the form of project-based Electronic Student Worksheets (e-SW) on thermochemical materials and to test their validity and practicality. Project-based e-SW on thermochemical materials was developed using the Plomp development model. The results of the material and media validation analysis were calculated using the Aiken's V formula and the results of the practicality analysis were calculated using the percentage of practicality. The results of material and media validation are 0.88 and 0.89 with very valid categories. The results of the practicality of students in the small group were 89.86% in the very practical category, while the practical results of students and teachers in the field test were 87.21% and 89.03% in the very practical category.